Structural and impedance spectroscopy study of Al-doped ZnO nanorods grown by sol-gel method - Muhammad, Kashif; Uda, Hashim, Prof. Dr.; Md. Eaqub, Ali; Ala'eddin Ahmad Jaber, Saif, Dr.; Syed Muhammad Usman, Ali; Willander, Magnus, Prof (Emerald Group Publishing Limited, 2013)
Link to publisher's homepage at http://www.emeraldinsight.com/